(untitled) (Scientific journal of the Fergana State University, 2025)
This article highlights ways to develop the physical qualities of children through the effective organization of gymnastics classes in physical education classes in general education institutions. It has been shown that gymnastics is one of the main means of children’s physical development, improving their health, and strengthening their health.